Hydrogen embrittlement resistant coated steel
Patent Information
- Application Number
- CN202080107931.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2040-12-17
AI Technical Summary
[0013]为了说明本发明的目的,采用马氏体钢作为优选实施方案钢,将所述马氏体钢制造成冷轧钢板以证明本发明的有益效果。使用马氏体钢一定不能被认为是对本发明的限制,并且当C、Mn、Al和Si中的任一者或更多者为合金元素时,可以对具有C、Mn、Al和Si中的任一者或更多者的任何钢实施本发明的方法。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004285030150000071
Abstract
Description
[0001] The present invention relates to a steel substrate with resistance to hydrogen embrittlement and a method for manufacturing the same, and particularly to a coated steel substrate with good resistance to hydrogen embrittlement.
[0002] High-strength steels, such as dual-phase (DP) steel, advanced high-strength steel (AHSS), ultra-high-strength steel (UHSS), or martensitic steel (MS), are characterized by their high tensile strength. Due to these properties, the use of such steels in automobile manufacturing has increased in response to the automotive industry's demands for weight reduction in motor vehicles without sacrificing passenger safety, particularly for structural components such as pillars and reinforcing components such as bumpers and crash beams, where further strength enhancements are required.
[0003] Furthermore, all the aforementioned steels used in automobiles also need to be resistant to hydrogen-induced delayed fracture, and are commonly referred to as hydrogen embrittlement resistant steels. Hydrogen embrittlement generally refers to the embrittlement caused by hydrogen generated during processing such as electroplating, electrolytic cleaning, or when the final product is used in corrosive environments or in atmospheres with high moisture content. This hydrogen diffuses into defective regions in the steel sheet, such as dislocations, pores, and grain boundaries, embrittles these defective regions, and leads to a deterioration in the ductility and rigidity of the steel sheet, resulting in fracture under static or dynamic stress.
[0004] Therefore, the object of the present invention is to solve these problems by making available methods and coated steel substrates suitable for use in the automotive industry and having a hydrogen embrittlement rate of less than 30%, preferably less than 25%, and more preferably less than 22%.
[0005] In a preferred embodiment, the steel substrate may have:
[0006] - Ultimate tensile strength greater than or equal to 900 MPa, preferably greater than 980 MPa
[0007] - Yield strength greater than or equal to 700 MPa, and preferably greater than 800 MPa.
[0008] Another object of the present invention is to make available a method for manufacturing these substrates, which is compatible with conventional industrial applications and robust to variations in manufacturing parameters.
[0009] For the purposes of this invention, the term "coated steel substrate" includes hot-rolled steel strip, cold-rolled steel sheet, flat steel products, tailor welded blank, and blank substrate containing one or more of C, Al, Si, and Mn as alloying elements and having a Ni-MoS2 layer thereon.
[0010] The present invention addresses the problem of hydrogen embrittlement by coating steel with a Ni-MoS2 layer, wherein the Ni-MoS2 layer has at least 0.3% MoS2 particles by weight and the thickness of the layer is equal to or greater than 0.1 micrometers.
[0011] The Ni-MoS2 layer of the present invention can withstand welding processes, enabling the Ni-MoS2 layer of the present invention to be welded for use in automobile manufacturing.
[0012] The method is described in detail herein to illustrate the invention. The method according to the invention can be produced by a method consisting of the sequential steps mentioned herein:
[0013] To illustrate the purpose of this invention, martensitic steel is used as the preferred embodiment steel, and the martensitic steel is manufactured into cold-rolled steel sheet to demonstrate the beneficial effects of this invention. The use of martensitic steel should not be considered a limitation of this invention, and the method of this invention can be applied to any steel having any one or more of C, Mn, Al, and Si when C, Mn, Al, and Si are alloying elements.
[0014] The coated steel substrate according to the invention can be produced by any of the following methods. A preferred method includes providing a semi-finished casting of steel having the chemical composition according to the invention. The casting can be made into ingots or continuously into the form of thin slabs or thin strips, i.e., the thickness ranges from about 220 mm for slabs to tens of millimeters for thin strips.
[0015] For example, slabs with the chemical composition of steel are manufactured by continuous casting, wherein the slab optionally undergoes direct light compression during the continuous casting process to avoid central segregation and ensure that the local carbon to nominal carbon ratio remains below 1.10. The slabs provided by the continuous casting process can be used directly at the high temperature after continuous casting, or they can be cooled to room temperature first and then heated for hot rolling.
[0016] The temperature of the slab undergoing hot rolling is at least 1000°C and at least 1280°C. A slab temperature exceeding 1150°C is preferred because below this temperature, excessive load is applied to the mill, and the steel temperature may drop to the ferrite transformation temperature during finishing rolling, resulting in the steel being rolled with transformed ferrite in its microstructure. Therefore, the slab temperature is preferably high enough that hot rolling can be completed in the temperature range of Ac3 to Ac3+100°C, and the final rolling temperature is maintained above Ac3. Reheating at temperatures above 1280°C must be avoided, as it is industrially expensive.
[0017] A final rolling temperature range of Ac3 to Ac3+100°C is preferred to achieve a microstructure favorable for recrystallization and rolling. The final rolling pass must be performed at a temperature greater than 850°C, as below this temperature, the steel sheet exhibits a significant decrease in rollability. The steel sheet obtained in this manner is then cooled to a coiling temperature below 650°C at a cooling rate greater than 30°C / second. Preferably, the cooling rate will be less than or equal to 200°C / second.
[0018] The hot-rolled steel sheet is then coiled at a coiling temperature below 650°C to avoid ovalization, and preferably below 625°C to avoid oxide scale formation. A preferred range for such coiling temperature is 400°C to 625°C. The coiled hot-rolled steel sheet is then cooled to room temperature and subsequently subjected to optional hot-roll annealing.
[0019] The hot-rolled steel sheet can be subjected to an optional scale removal step to remove the scale formed during hot rolling before optional hot-roll annealing. The hot-rolled steel sheet can then be subjected to optional hot-roll annealing at a temperature of 400°C to 750°C for at least 12 hours and no more than 96 hours, with the temperature held below 750°C to avoid partial transformation of the hot-rolled microstructure and thus loss of microstructure uniformity. Subsequently, the optional scale removal step of the hot-rolled steel sheet can be performed by, for example, pickling of such a steel sheet. The hot-rolled steel sheet is then subjected to cold rolling at a reduction rate of 35% to 90% to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is then obtained.
[0020] Subsequently, the cold-rolled steel is sent to a continuous annealing cycle for heat treatment, which will impart the desired properties and microstructure to the steel of the present invention.
[0021] In the annealing of cold-rolled steel sheets, the cold-rolled steel sheets are heated to a homogenization temperature of Ac1 to Ac3+100°C at a heating rate greater than 2°C / second, preferably greater than 3°C / second, wherein Ac1 and Ac3 of the composite steel sheets are calculated by experimental dilatation studies.
[0022] The cold-rolled steel sheet is held at a homogenization temperature for 10 to 500 seconds to ensure complete recrystallization of the initially work-hardened microstructure. The cold-rolled steel sheet is then cooled to a temperature below 550°C, and preferably below 500°C, at a cooling rate greater than 5°C / second, and optionally held at 150°C to 500°C for 10 to 1000 seconds to impart the microstructure desired by the present invention. The cold-rolled steel sheet is then cooled to obtain a cold-rolled steel substrate.
[0023] The cold-rolled steel substrate is then immersed in an acidic pickling solution for 5 to 100 seconds at a temperature range of 30°C to 100°C to activate the surface for electroplating.
[0024] A Ni-MoS2 layer is then electroplated onto the surface of the cold-rolled steel substrate. The Ni-MoS2 layer consists of a nickel matrix in which MoS2 particles are embedded. The MoS2 particles must constitute more than 0.3% by weight of the total coating to impart sufficient resistance to hydrogen embrittlement to the coated steel substrate, and preferably 0.4% or greater, and more preferably equal to or greater than 0.5%. In a preferred embodiment, the presence of MoS2 can be limited to 3% for economic reasons.
[0025] A Ni-MoS2 layer is electroplated onto a cold-rolled steel substrate to obtain resistance to hydrogen embrittlement by coating with an electroplating solution containing NiSO4 and MoS2, wherein the concentration of NiSO4 is from 100 g / L to 500 g / L and the concentration of MoS2 is from 1 g / L to 15 g / L. The concentration of MoS2 is maintained at 1 g / L to 15 g / L because the presence of MoS2 above 15 g / L during electroplating would reduce the efficiency of Ni deposition due to the enhanced hydrogen evolution reaction during electroplating. The concentration range of NiSO4 is optimized to obtain sufficient Ni deposition during electroplating and to allow MoS2 particles to embed within the deposited Ni matrix. A preferred concentration of MoS2 is from 2 g / L to 14 g / L, and more preferably from 3 g / L to 12 g / L. A preferred concentration of NiSO4 is from 100 g / L to 400 g / L, and more preferably from 150 g / L to 400 g / L.
[0026] Apply 15 A / dm during electroplating 2 Up to 45A / dm 2 The current density is applied for 30 to 300 seconds to allow MoS2 particles, at a weight percentage of 0.3% or greater, to embed into the nickel matrix of the Ni-MoS2 layer, and the thickness of the Ni-MoS2 layer is at least 0.1 micrometers. Preferably, the layer thickness is greater than 0.2 micrometers, and more preferably greater than 0.3 micrometers. If the current density is less than 15 A / dm³... 2 If this is not done properly, MoS2 particles of 0.3% or greater by weight will not be able to embed into the Ni matrix, thus preventing the formation of the final Ni-MoS2 layer. The electroplating temperature for cold-rolled steel substrates is typically maintained between 30°C and 90°C, while the pH of the plating solution is maintained between 2 and 6. The preferred range for the current density during electroplating is 15 A / dm³. 2 Up to 40A / dm 2 And more preferably A / dm 2 Up to 38A / dm 2 The preferred electroplating time is 50 to 250 seconds, and more preferably 60 to 200 seconds.
[0027] Subsequently, the cold-rolled steel substrate is rinsed with any suitable solvent, such as ethanol, and dried with, for example, hot air to obtain a coated steel substrate.
[0028] The steel substrate can then be coated using any known industrial process, such as electroplating, JVD, and PVD.
[0029] Then, optional post-batch annealing can be carried out at a temperature of 150°C to 300°C for 30 minutes to 120 hours.
[0030] In a preferred embodiment, the chemical composition of the steel substrate used in the method according to the present invention is as follows:
[0031] Carbon is present in the form of 0.05% to 0.5%. Carbon is an essential element for improving the strength of the steel of the present invention by generating low-temperature transformation phases such as martensite and bainite. Furthermore, carbon plays a crucial role in austenite stabilization; therefore, it is an essential element for ensuring retained austenite. Thus, carbon plays two key roles: one is for increasing strength, and the other is for retaining austenite to impart ductility. However, a carbon content of less than 0.05% will not be sufficient to stabilize the austenite required for the steel of the present invention. On the other hand, when the carbon content exceeds 0.5%, the steel exhibits poor spot weldability, which limits its application in automotive parts.
[0032] Manganese is present in the steel of the present invention at a concentration of 0.2% to 5%. This element is a gammagenous phase-forming element. The purpose of adding manganese is essentially to obtain a microstructure containing austenite. Manganese is an element that stabilizes austenite at room temperature to obtain retained austenite. A minimum of about 0.2% by weight of manganese is required to provide strength and hardenability to the steel of the present invention, as well as to stabilize austenite. Therefore, the present invention preferably uses a higher percentage of manganese, such as 2% or more. However, when the manganese content is greater than 5%, it has adverse effects, such as hindering the transformation of austenite during cooling after annealing, which hinders the formation of other microstructure components. Additionally, a manganese content above 5% also degrades the weldability of the steel of the present invention and may prevent the achievement of ductility targets.
[0033] The steel of the present invention has a silicon content of 0.1% to 2.5%. Silicon is a component that can inhibit the precipitation of carbides during overaging; therefore, austenite is stable at room temperature due to the presence of silicon. Furthermore, due to the poor solubility of silicon in carbides, it effectively inhibits or hinders carbide formation, thus also promoting the formation of low-density carbides in the bainitic structure, which endows the steel of the present invention with its basic mechanical properties, such as tensile strength. However, an unbalanced silicon content will not produce the aforementioned effects and will lead to problems such as temper embrittlement. Therefore, the concentration is controlled within the upper limit of 2.5%.
[0034] The aluminum content is 0.01% to 2%. In this invention, aluminum removes oxygen present in the molten steel to prevent oxygen from forming a gaseous phase during solidification. Aluminum also fixes nitrogen in the steel to form aluminum nitride, thereby reducing grain size. Higher aluminum content (above 2%) raises the Ac3 point to higher temperatures, thus reducing productivity. When adding a high manganese content, an aluminum content of 0.8% to 1% can be used to balance the effect of manganese on the evolution of transformation point and austenite formation with temperature.
[0035] Sulfur is not an essential element, but may be present in steel as an impurity. From the perspective of this invention, the sulfur content is preferably as low as possible, but from the perspective of manufacturing costs, a sulfur content of 0.09% or less is preferable. Furthermore, if a high level of sulfur is present in the steel, it will combine with manganese, in particular, to form sulfides and reduce the beneficial effects of manganese on this invention.
[0036] The phosphorus content of the steel of the present invention is 0.002% to 0.09%. Phosphorus reduces weldability and hot ductility, particularly due to its tendency to segregate at grain boundaries or co-segregate with manganese. For these reasons, its content is limited to 0.09%, and preferably below 0.06%.
[0037] To avoid material aging and to minimize the precipitation of aluminum nitrides during solidification, which is detrimental to the mechanical properties of steel, nitrogen is limited to 0.09%.
[0038] The composite strip coil of the steel of the present invention has a chromium content of 0% to 1%. Chromium is a fundamental element that provides strength and hardening to steel, but when used at a concentration higher than 1%, it impairs the surface finish of the steel. Furthermore, a chromium content below 1% coarsens the dispersion pattern of carbides in the bainitic structure, thus keeping the density of carbides in the bainitic structure low.
[0039] Nickel can be added as an optional element in amounts of 0% to 1% to increase the strength and improve the toughness of steel. A minimum of 0.01% is required to achieve this effect. However, when its content exceeds 1%, nickel leads to a deterioration in ductility.
[0040] Copper can be added as an optional element in amounts of 0% to 1% to increase the strength of steel and improve its corrosion resistance. A minimum of 0.01% is required to achieve this effect. However, when its content exceeds 1%, it can degrade the surface appearance.
[0041] Molybdenum is an optional element comprising 0% to 0.5% of the steel of this invention; molybdenum plays an effective role in improving the hardenability of the steel. However, excessive addition of molybdenum increases the cost of adding alloying elements, therefore its content is limited to 0.4% for economic reasons.
[0042] Niobium is present in the steel of the present invention at 0% to 0.1% and is suitable for forming carbonitrides to impart strength to the steel of the present invention through precipitation hardening. Niobium also affects the size of the microstructure components by its precipitation as carbonitrides and by inhibiting recrystallization during the heating process. Therefore, a finer microstructure formed at the end of the holding temperature and thus after full annealing will cause hardening of the product. However, due to the observed saturation effect of its effect (meaning that an additional amount of niobium will not cause any improvement in the strength of the product), a niobium content above 0.1% is not economically of concern.
[0043] Titanium, like niobium, is added to the steel of the present invention at 0% to 0.1%, participating in the carbonitrides and thus playing a role in hardening. However, it also forms titanium nitrides that appear during the solidification of the cast product. The amount of titanium is therefore limited to 0.1% to avoid the formation of coarse titanium nitrides that are detrimental to formability. At titanium content below 0.001%, there is no effect on the steel of the present invention.
[0044] The calcium content in the steel of the present invention is from 0.001% to 0.005%. Calcium is added to the steel of the present invention as an optional element, especially during inclusion treatment. Calcium contributes to the refining of the steel by preventing the harmful effects of sulfur from forming spherical sulfur contents.
[0045] Vanadium effectively increases the strength of steel by forming carbides or carbonitrides, and from an economic point of view, its upper limit is 0.1%. Other elements such as cerium, boron, magnesium, or zirconium can be added alone or in combination in the following proportions: cerium ≤ 0.1%, boron ≤ 0.003%, magnesium ≤ 0.010%, and zirconium ≤ 0.010%. These elements, up to the maximum content levels shown, allow for grain refinement during solidification. The remaining composition of steel consists of iron and unavoidable impurities resulting from processing.
[0046] The microstructure of the coated steel substrate may contain any one or more of retained austenite, martensite, tempered martensite, tempered bainite, ferrite, and bainite. These micro-components may account for 90% or more of the microstructure of the coated steel substrate of the present invention. In addition to the microstructures described above, microstructure components such as pearlite and cementite may also be present in the coated steel substrate, but are limited to a total maximum of 10%. Example
[0047] The following tests, embodiments, graphical examples, and tables presented herein are non-limiting in nature and must be considered for illustrative purposes only, and will demonstrate advantageous features of the invention.
[0048] Table 1 summarizes steels with different compositions, showing two example steel compositions, steel A and steel B, while Table 2 shows the implementation parameters for the NiMoS2 coating. Subsequently, Table 3 summarizes the microstructure of the steel sheets obtained during the tests, and Table 4 summarizes the evaluation results obtained for hydrogen embrittlement and mechanical properties.
[0049] Table 1
[0050]
[0051] Table 2
[0052] Table 2 summarizes the coating parameters applied to the steels in Table 1 to coat them into hydrogen-resistant steels. Steel combinations I1 to I6 are used to manufacture the hydrogen-resistant steels according to the invention. The table also specifies reference steels, designated by R1 to R4. Before coating, both the inventive steel and the reference steel are hot-rolled at a finishing temperature of 890°C, then coiled at 620°C, and subsequently cold-rolled at a reduction rate of 60%. The cold-rolled steel is annealed at 880°C and then cooled to room temperature to obtain annealed cold-rolled steel sheets, which are then coated with a NiMoS2 coating according to the conditions mentioned in Table 2 to obtain hydrogen-resistant steels.
[0053] Table 2 is as follows:
[0054]
[0055] I = according to the invention; R = reference; underlined value: not according to the invention.
[0056] Table 3 illustrates the results of tests conducted to clearly illustrate the inventive features of the method of the present invention, wherein key parameters of the NiMoS2 layer were determined by SEM cross-sectional measurements, and the concentration of MoS2 was measured by the GDOES method. All experimental microstructures were fully martensitic.
[0057] Table 3
[0058]
[0059] I = according to the invention; R = reference; underlined value: not according to the invention.
[0060] Table 4 illustrates the results of tests conducted to demonstrate the mechanical properties, and the hydrogen embrittlement resistance was measured using the method published in the journal publication entitled "Graphene coating as a protective barrier against hydrogen embrittlement" in International Journal of Hydrogen Energy 39 (2014), pp. 11810-11817, with respect to the hydrogen embrittlement ratio of the inventive steel and the reference steel.
[0061] The results are recorded in this article:
[0062]
[0063]
[0064] I = according to the invention; R = reference; underlined value: not according to the invention.
Claims
1. A method for producing coated steel substrate, comprising the following steps: Provide steel base material; An electroplating solution with a pH of 2 to 6 containing 100 g / L to 500 g / L NiSO4 and 1 g / L to 15 g / L MoS2 was applied by applying 15 A / dm 2 Up to 45A / dm 2 The steel substrate is electroplated with a current density for a duration of 30 to 300 seconds to form a Ni-MoS2 coating layer, wherein the Ni-MoS2 coating has a thickness of 0.1 micrometer to 0.7 micrometer and the Ni-MoS2 layer contains at least 0.3% MoS2 particles by weight percentage. Subsequently, the steel substrate is rinsed and dried to obtain a coated steel substrate.
2. The method according to claim 1, wherein the pH of the electroplating solution is 2 to 5.
3. The method according to claim 1 or 2, wherein the concentration of NiSO4 in the electroplating solution is from 100 g / L to 400 g / L.
4. The method according to any one of claims 1 to 3, wherein the concentration of MoS2 in the electroplating solution is from 1 g / L to 15 g / L.
5. A method for producing a coated steel substrate according to any one of claims 1 to 4, wherein the steel substrate undergoing the electroplating step is a cold-rolled steel sheet obtained through the following steps: Provide semi-finished steel products; The semi-finished product is then reheated to a temperature of 1000°C to 1280°C; The semi-finished product is rolled in the austenitic region to obtain hot-rolled steel sheet, wherein the final hot rolling temperature should be higher than 850°C; The steel sheet is cooled to a coiling temperature below 650°C at an average cooling rate of above 30°C / second; and the hot-rolled steel sheet is coiled. The hot-rolled steel sheet is cooled to room temperature; Optionally, the hot-rolled steel sheet is subjected to an oxide scale removal step; The hot-rolled steel sheet may be annealed at a temperature of 400°C to 750°C. Optionally, the hot-rolled steel sheet is subjected to an oxide scale removal step; The hot-rolled steel sheet is cold-rolled at a reduction rate of 35% to 90% to obtain a cold-rolled steel sheet; Then, the cold-rolled steel sheet is annealed by heating it at a rate greater than 2°C / second to a homogenization temperature of Ac1 to Ac3+100°C, and the cold-rolled steel sheet is held at the homogenization temperature for 10 seconds to 500 seconds. The steel sheet is then cooled to a temperature below 550°C at a rate greater than 5°C / second, wherein the cold-rolled steel sheet can optionally be held at a temperature range of 150°C to 500°C for 10 to 1000 seconds during the cooling process to obtain a cold-rolled steel substrate. Then, the cold-rolled steel substrate is pickled for 5 to 100 seconds at a temperature range of 30°C to 100°C.
6. The coated steel substrate according to claim 1, wherein the Ni-MoS2 layer has a thickness of at least 0.2 micrometers.
7. The coated steel substrate according to claim 1, wherein the Ni-MoS2 layer comprises at least 0.4% MoS2 particles by weight percentage.
8. The coated steel substrate according to claim 6 or 7, wherein the hydrogen embrittlement rate of such coated steel substrate is less than 30%.
9. The coated steel substrate according to any one of claims 6 to 8, wherein the coated steel substrate is a cold-rolled steel sheet, and the cold-rolled steel sheet comprises, by weight percentage, the following elements: And it can contain one or more of the following optional elements: The remaining components consist of iron and unavoidable impurities resulting from processing.
10. The coated steel substrate according to any one of claims 6 to 9, wherein the substrate has an ultimate tensile strength of 900 MPa or greater and a yield strength of 700 MPa or greater.
11. Use of a coated steel substrate obtainable by any one of claims 1 to 5 or a coated steel substrate obtainable by any one of claims 6 to 10 for manufacturing structural components of a vehicle.
Citation Information
Patent Citations
Preparation method of composite coating layer containing nano MoS2 solid particles
CN101831676A
Cold rolled and heat treated steel sheet and a method of manufacturing thereof
CN111417738A
